Problems of Mathematics Learning in Class V Elementary School Students at SDN Karang Anyar II - Dliyaul Laudza'; Agung Setyawan (Citra Dharma Cindekia, 2022)
This research departs from the background of the low learning outcomes achieved by fifth grade students at SDN Karang Anyar II Karang Anyar village, Kec. District border. Probolinggo. One of the subjects considered difficult by students is mathematics. So that this lesson is less attractive to students. This problem causes many students to experience difficulties in learning mathematics. From the results of initial observations, it can be seen that the cause of this is because students feel bored, bored with the implementation of learning with a traditional learning approach which in the end makes students look for other activities to relieve their boredom which causes the class atmosphere to be not conducive. This study aims to determine the problems in learning mathematics for students at SDN Karanganyar II on the mathematics learning achievement of fifth grade students at SDN Karang Anyar II, Karang Anyar Village, Bantaran District. To achieve the above objectives, a qualitative approach is used with the type of descriptive analysis approach.